ASAP1 Promotes Epithelial to Mesenchymal Transition by Activating the TGFβ Pathway in Papillary Thyroid Cancer - Shiji Song; Zixing Leng; Xinxin Zhao; Ziping Liu; Yongshuai Li; Wenjing Zhang; Junming Yue; Yuxia Fan (Cancer Medicine)
ABSTRACT Background Papillary thyroid cancer (PTC) is the most common type of thyroid malignancy. While the prognosis of PTC is generally favorable, some cases exhibit aggressive behavior, leading to metastasis and recurrence. ASAP1 (ArfGAP with SH3, ankyrin repeats, and PH domain 1), an ADP‐ribosylation factor GTPase‐activating protein, has been implicated in tumor metastasis. However, its role in PTC remains unclear. Methods ASAP1 expression in PTC was evaluated using TCGA and GEO databases. Studies in PTC cell lines (MDA‐T32 and MDA‐T85) included lentiviral‐mediated knockdown and overexpression of ASAP1 to assess effects on epithelial–mesenchymal transition (EMT) marker expression, cell proliferation, and invasive capacity. TGFβ pathway activity was examined by p‐SMAD2 Western blotting and luciferase reporter assays. ASAP1‐SMAD2/3 interactions were analyzed using co‐immunoprecipitation (CO‐IP) and immunofluorescence. Results ASAP1 was aberrantly upregulated in PTC. Lentiviral knockdown of ASAP1 in PTC cells suppressed the EMT process. Reduced ASAP1 expression also inhibited cell survival, proliferation, migration, invasion, and the expression of p‐SMAD2 in the TGFβ pathway in PTC cells. Conversely, ASAP1 overexpression reversed these effects. Mechanistically, ASAP1 interacts with the SMAD2/3 complex, forming a positive feedback loop with TGFβ signaling that promotes EMT and cell invasiveness in PTC cells, which suggests its potential role in PTC metastasis. Conclusions These findings suggest that targeting ASAP1 may offer a novel therapeutic strategy to limit PTC metastasis by suppressing EMT and attenuating the TGFβ pathway.